Konferencja naukowa: „Profesor Jan Baszkiewicz - człowiek Uniwersytetu” - Olszewski, Henryk (Czasopismo Prawno-Historyczne, 2018)
Konferencja naukowa: „Profesor Jan Baszkiewicz - człowiek Uniwersytetu”